1996
DOI: 10.1002/art.1780391212
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative rate of relapse of lupus nephritis after successful treatment with cyclophosphamide

Abstract: Objective. To determine the cumulative rate of relapse of lupus nephritis that has been treated successfully with cyclophosphamide (CYC), and to estimate the association between time to relapse and demographic, clinical, laboratory, and treatment variables.Methods. This was an observational study of 48 systemic lupus erythematosus (SLE) patients who were treated successfully with CYC between 1979 and 1993 and followed up thereafter a t 3 university hospitals. Demographic and clinical variables, laboratory data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
3
7

Year Published

2000
2000
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 37 publications
4
56
3
7
Order By: Relevance
“…The definitions for remission, often referred to as complete, range from those that require a reduction in proteinuria to essentially normal levels Ͻ0.3 to 0.5 g/d (6,8,(27)(28)(29)(30) to those that require improvement to Յ1.0 g/d (9,31) and those that require only a Ն30% reduction in proteinuria to Ͻ3 g/d (32). In addition, renal function as measured by serum creatinine level must be normal in some studies (6,27), whereas in others, it must be "stable" (i.e., Ͻ30% rise in serum creatinine) or "improved" (9,28) or there must be a lack of doubling serum creatinine (31). In our study, we chose to apply the term CR to patients who achieved a normalization in renal function and proteinuria because the outcome for these patients is significantly improved over that for patients with NR.…”
Section: Discussionmentioning
confidence: 99%
“…The definitions for remission, often referred to as complete, range from those that require a reduction in proteinuria to essentially normal levels Ͻ0.3 to 0.5 g/d (6,8,(27)(28)(29)(30) to those that require improvement to Յ1.0 g/d (9,31) and those that require only a Ն30% reduction in proteinuria to Ͻ3 g/d (32). In addition, renal function as measured by serum creatinine level must be normal in some studies (6,27), whereas in others, it must be "stable" (i.e., Ͻ30% rise in serum creatinine) or "improved" (9,28) or there must be a lack of doubling serum creatinine (31). In our study, we chose to apply the term CR to patients who achieved a normalization in renal function and proteinuria because the outcome for these patients is significantly improved over that for patients with NR.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the incidence of renal fl ares of lupus nephritis after initial remission with steroid and cyclophosphamide treatment [2,[4][5][6]14]. Ciruelo et al [14] described a cumulative rate of renal relapse of 46 % at 10 years in patients treated with corticosteroid and cyclophosphomide for a median of 31 months.…”
Section: Discussionmentioning
confidence: 99%
“…Increased time to first renal remission predicts an earlier relapse or renal flare, with rate of renal flare and subsequent response to treatment predicting a worse renal outcome in the longer term [16, 17]. In addition, increased delay to treatment of nephritis with CYC has been found to reflect a group of patients with an increased time to renal remission and higher relapse rate [16]. This suggests that better outcomes might be obtained with a drug like MMF that provides similar rates of renal remission with less toxic adverse effects and thus might be instituted earlier after diagnosis of lupus nephritis than CYC.…”
Section: Discussionmentioning
confidence: 99%